Pengaruh Senam Otak (Brain Gym) Terhadap Konsentrasi pada Anak di SD Negeri Kerten II Surakarta - Nada Nurmalasari; Tri Susilowati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The biggest problem experienced by children during learning is lack of concentration. The survey results showed that 73% of elementary school children felt less concentrated. This can be prevented by increasing movement and thought activities that involve the right and left brain. One of them is the brain gym method. Brain gym is a collection of simple movements that aim to connect or unite the mind and body. The aim of the study was to analyze the effect of brain gym on concentration in children at SD Negeri Kerten II Surakarta. The research method is Quasi Experimental Design with a research design of One Group Pre-test and Post-test Design. The sampling technique is total sampling with a total of 36 samples. The research instrument used the Grid Concentration Test. Univariate and bivariate data analysis. The results showed that the majority before the intervention was in the category of very low concentration after the intervention was in the moderate concentration category. The conclusion of the study is that there is an effect of brain gym on concentration in children at SD Negeri Kerten II Surakarta.